KEUNGGULAN BERSAING KOPERASI BERKAITAN DENGAN PENERAPAN INTELLECTUAL CAPITAL, MANAJEMEN KEANGGOTAAN, DAN PARTISIPASI ANGGOTA - Gemina, Dwi; ., Samsuri; Kusuma, Indra Cahya (Jurnal Manajemen dan Kewirausahaan, 2013)
The objectives of this study were to determine intellectual capital application, membership management and member participation effects in Cooperative competitive advantage. Questionnaires were distributed to 208 respondents. The Successive Intervals method was used in order to convert ordinal scale of measurement to be interval measurement level. The Research model was a path analysis and the results of this study showed that the intellectual capital, membership management and member participation simultaneously and partially affected competitive advantage.